Studying the evaluation of the conditions of hosting international sport events in Iraq - Jabar Matar AL-Bkhati, Maytham; Aziz Dawood Al-Sudani, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to know the conditions for organizing tournaments such as football or any other sport and Olympic Games, whether continental or international. The researcher adopted the descriptive method survey method to solve the problem, and the sample included research faculty and students of Maysan University, where the number of colleges is 8 and the number of the sample is 140. The researcher used the statistical bag SPSS and extracted the weighted average and the percentage weight of the questionnaire sections that got a good level, and the conclusions and recommendations were that an increase in the size of crises and obstacles facing the establishment of sporting events requires professional management to face these obstacles and develop plans and future solutions and benefit from all human and material potentials and invest in the best ways and prepare for future crises.